(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Purpose to evaluate the remineralization effect of the Chicken egg shell powder on primary teeth with induced caries-like lesions. Materials and methods the current experimental in-vitro study was performed on twenty dentin specimens prepared from twenty fresh extracted deciduous and stored in simulated body fluid. EDTA treated the dentin specimens as a demineralized agent for two hours, washed them with water, dried them, and analyzed them by SEM and EDX. After that, the dentin specimens were immersed in the Chicken egg shell powder solution as a remineralizing agent and finally analyzed by SEM and EDX. Results By a Comparison of atom mass percent in the different observation times (blank sample, after demineralization process, and after remineralization process, it was revealed that the main value of the calcium of the blank dentin samples was significantly decreased after demineralization by EDTA (3.48±1.33), (p=0.000) then significantly increased after remineralization by the Chicken egg shell powder (25.9±5.82), (p=0.000). Conclusion the Chicken egg shell powder has a great power of remineralization as it deposits Calcium, phosphorous, and magnesium minerals on the demineralized dentin surface.